Polyphyllin II suppresses cell migration, invasion, and metastasis by inducing cytoskeletal rearrangement through the ROCK1/LIMK/CFL1 pathway in bladder cancer cells - Zhiyong Liu; Zhonghua Sun; Yuning Xie; Yaxin Shi; Guanghui Pan; Minmin Yu; Zilu Wang; Han Cao; Yang Liu; Quanlai Qiao; Changjing Chen; Xiangdong Xu; et al. (Compuscript Ltd, 2024)
This study was aimed at determining the antimetastatic effect of polyphyllin II (PPII) in bladder cancer (BC) and the underlying mechanisms in vitro and in vivo . Wound healing, Transwell assays, and phalloidin staining were performed to determine the effects of PPII on BC cell migration, invasion, and cytoskeletal formation. Gene transcription and expression changes were detected via RNA sequencing and western blotting. The subchronic toxicity and antimetastatic effects of PPII were evaluated in Nu/Nu nude mice. PPII inhibited the migration and invasion of BC cells. Bioinformatics analysis indicated that cytoskeletal regulation was a potentially regulated process. PPII restrained cytoskeletal formation, as confirmed by phalloidin staining. Mechanistically, PPII was found to decrease p-LIMK1/2 and p-CFL1 expression through ROCK1, and to inhibit increased p-CFL1 levels and invasion and migration abilities of BC cells induced by constitutively active RHOA. Subchronic toxicity evaluation revealed that 3.0 mg/kg PPII had limited effects on tissue morphology, alkaline phosphatase, alanine aminotransferase, and aspartate aminotransferase. Furthermore, PPII treatment effectively inhibited the formation of pulmonary metastatic nodules, as well as the expression of ROCK1, p-LIMK1, and p-CFL1 in the lungs. Thus, PPII inhibits BC cell invasion, migration, and metastasis through the RHOA-ROCK1-LIMK1/2-CFL1 axis, and is a potential candidate for antimetastatic drug development.